Artificial Intelligence in Personalized Marketing: Strategies for Enhancing Consumer Engagement - Syaharuddin; Nur Fitri Hidayanti; Dedy Iswanto; Nurul Hidayati Indra Ningsih (Advance Sustainable Science Engineering and Technology, 2025)
This study examines the use of artificial intelligence (AI) in personalized marketing to boost consumer engagement. Using a systematic literature review from Scopus, DOAJ, and Google Scholar, it finds that AI helps predict consumer behavior, optimize communication, and deliver real-time adaptive content. These capabilities enhance customer satisfaction and loyalty. However, challenges such as data privacy, ethical concerns, and the need for human oversight remain. The study recommends investing in AI-driven analytics, automation, and dynamic content strategies to improve customer experience and interaction.